2008
DOI: 10.1158/0008-5472.can-08-2665
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide Allelic State Analysis on Flow-Sorted Tumor Fractions Provides an Accurate Measure of Chromosomal Aberrations

Abstract: Chromosomal aberrations are a common characteristic of cancer and are associated with copy number abnormalities and loss of heterozygosity (LOH). Tumor heterogeneity, low tumor cell percentage, and lack of knowledge of the DNA content impair the identification of these alterations especially in aneuploid tumors. To accurately detect allelic changes in carcinomas, we combined flow-sorting and single nucleotide polymorphism arrays. Cells derived from archival cervical and colon cancers were flow-sorted based on … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
51
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 31 publications
(52 citation statements)
references
References 41 publications
(42 reference statements)
1
51
0
Order By: Relevance
“…LOH encompassed 15.7% of the genome, including several entire chromosome arms (5p, 6q, Xp, Xq) or large distal portions (2q, 3q, 6p, 11q, 13q, 19p, 22q) (Supplementary Fig. 7, Supplementary Table 9), consistent with previous descriptions of LOH in cervical carcinomas 17 . The overall profile is consistent with published karyotypes of various HeLa strains 4 , suggesting that the hypertriploid state arose either during tumorigenesis or early in the establishment of the HeLa cell line.…”
supporting
confidence: 88%
“…LOH encompassed 15.7% of the genome, including several entire chromosome arms (5p, 6q, Xp, Xq) or large distal portions (2q, 3q, 6p, 11q, 13q, 19p, 22q) (Supplementary Fig. 7, Supplementary Table 9), consistent with previous descriptions of LOH in cervical carcinomas 17 . The overall profile is consistent with published karyotypes of various HeLa strains 4 , suggesting that the hypertriploid state arose either during tumorigenesis or early in the establishment of the HeLa cell line.…”
supporting
confidence: 88%
“…Genomic analysis of cellular subpopulations that differ in ploidy has been performed in other cancers, including breast [37], cervical, colorectal [14], prostate and pancreas [3, 45]. Compared with other genomic techniques, such as gene expression arrays and next-generation sequencing, which measure signals from a complex mixture of cell types, our approach has the advantage to dissect this complex mixture into distinct tumour clones and stromal cells.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that FACS can be used to separate tumor cells by ploidy for genomic analysis (Corver et al 2008). FACS separates subpopulations of tumor cells, and tumor cells from normal cells, by differences in their total genomic DNA content, or ploidy.…”
Section: Copy Number Analysis Of Tumors By Sector and Ploidymentioning
confidence: 99%